Graphics design work: service / Syarifah Damia Ahmad Jais - Ahmad Jais, Syarifah Damia (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Fun factor, Kuching's inaugural indoor theme park, promises amusement for all ages. To enhance its recognition, it will be adopting a strategic approach that infused a pixel theme and illustrative design across corporate branding, advertising, and multimedia, these elements will solidify its identity as the premier destination for fun and fitness. The Pixel-theme amplifies the park's image, while strategic advertisements will be used to attract tourists, and an emotive TV commercial will foster a deeper connection, enticing both locals and tourists to experience the joyous ambience firsthand. Fun factor, where fun meets innovation.